Hanging the mirror the discipline of reflective leadership - Scheffer, Alan; Scheffer, Mark; Braun, Nancy
Three management consultants take a fresh look at business leadership in a work that will enlighten and inspire. ....The premise that leaders need to be "reflective" to be effective is played out in finely tuned, well-organized chapters....The authors' keen insights, enhanced by liberal use of authoritative sources, pervade each chapter, offering leaders much to ponder....with relevant examples, sound counsel and end-of-chapter questions. Deftly written and researched, perceptive and relevant; an important addition to leadership literature.